Photochemical Strain‐Release‐Driven Cyclobutylation of C(sp3)‐Centered Radicals. Issue 7 (6th November 2019) - Ernouf, Guillaume; Chirkin, Egor; Rhyman, Lydia; Ramasami, Ponnadurai; Cintrat, Jean‐Christophe
Abstract: A new photoredox‐catalyzed decarboxylative radical addition approach to functionalized cyclobutanes is described. The reaction involves an unprecedented formal Giese‐type addition of C(sp 3 )‐centered radicals to highly strained bicyclo[1.1.0]butanes. The mild photoredox conditions, which make use of a readily available and bench stable phenyl sulfonyl bicyclo[1.1.0]butane, proved to be amenable to a diverse range of α‐amino and α‐oxy carboxylic acids, providing a concise route to 1, 3‐disubstituted cyclobutanes. Furthermore, kinetic studies and DFT calculations unveiled mechanistic details on bicyclo[1.1.0]butane reactivity relative to the corresponding olefin system. Abstract : High‐lying SOMO radicals, generated in situ under visible‐light photoredox conditions, undergo an efficient addition to highly strained bicyclo[1.1.0]butanes, providing a straightforward access to valuable alkylated cyclobutanes.